The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/pathogens9030219
|View full text |Cite
|
Sign up to set email alerts
|

Combined Amoebicidal Effect of Atorvastatin and Commercial Eye Drops against Acanthamoeba castellanii Neff: In Vitro Assay Based on Mixture Design

Abstract: The establishment of an effective therapeutic agent against Acanthamoeba keratitis (AK), remains until present, an issue to be solved due to the existence of a cyst stage in the life cycle of Acanthamoeba. Moreover, the effectiveness of the current standard therapeutic agents varies depending on the tested Acanthamoeba strains and its resistance pattern. In the present study, two 10-point augmented simplex-centroid designs were used to formulate a three-component mixture system using water, atorvastatin, and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Combination therapy of antibiotics plus antibiotics or other bio-active compounds to treat infectious diseases such as tuberculosis is gradually becoming a subject of interest and applied to others. Currently, treatment of Acanthamoeba infections comprises of drug combination therapy of biguanides, amidines, and azoles (Sifaoui et al, 2020). Also, synergistic effects of chlorhexidine plus cationic carbosilane dendrimers against A. polyphaga trophozoites and cysts have been documented (Heredero-Bermejo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination therapy of antibiotics plus antibiotics or other bio-active compounds to treat infectious diseases such as tuberculosis is gradually becoming a subject of interest and applied to others. Currently, treatment of Acanthamoeba infections comprises of drug combination therapy of biguanides, amidines, and azoles (Sifaoui et al, 2020). Also, synergistic effects of chlorhexidine plus cationic carbosilane dendrimers against A. polyphaga trophozoites and cysts have been documented (Heredero-Bermejo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Also, synergistic effects of chlorhexidine plus cationic carbosilane dendrimers against A. polyphaga trophozoites and cysts have been documented (Heredero-Bermejo et al, 2016). Essentially, herbal-based combinations could reduce drugs cytotoxicity, cost effect, and the requirement for long-term treatment (Sifaoui et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The ideal combination that reduced the parasite growth without causing cytotoxicity was 30% Optiben, 63.5% atorvastatin, and 3.1% water. In addition, the most effective combination that inhibited the parasite growth with limited cytotoxicity was 17.6% Diclofenaco-lepori and 82.4% atorvastatin [84]. Another study reported low EC 50 values for prodigiosin (2.2 µM) and obatoclax (0.5 µM) against A. castellanii trophozoites [85].…”
Section: Improvements In Existing Drugsmentioning
confidence: 99%
“…Theoretically speaking, as there are 1,800,000 contact lens wearers in Italy, infections with Acanthamoeba would be around 180 per year. 7 Acanthamoeba Keratitis occurs in young and immunocompetent individuals, most of whom are contact lens wearers and it equally affects men and women. The pathology occurs more frequently unilaterally, although bilateral cases have also been observed and the main risk factors that seem to be implicated in the onset of Acanthamoeba keratitis are; previous corneal trauma, cleaning of contact lenses with tap water or a solution contaminated with Acanthamoeba and the use of contact lenses.…”
Section: Brief Reviewmentioning
confidence: 99%